Velünk élő történelem I. / Aki magyar, velünk tart
3 parts long documentary film about the "conter-revolution" in Hungary, interviews with communist politicians, former freedom fighters, historians and soldiers. Co-operaters: Valéria Benke, Antal Apró, Péter Eedős, Róbert Bohó, Béla Biszku, György Marosán, László Földes, András Hegedűs, György Szepesi, Jenő Hazai, György Kalmár, Tibor Zinner, Tivadar Pártay, Lajos Tóth, Dezső Radványi, Mihály Kornidesz Ervin Hollós, János Berecz, János Molnár